2021
DOI: 10.1155/2021/2508956
|View full text |Cite
|
Sign up to set email alerts
|

Appendiceal Diverticulitis in a Young Female Diagnosed on Pathology after Laparoscopic Appendectomy for Acute Appendicitis

Abstract: Background. Appendiceal diverticulitis is a rare cause of inflammation of the appendix, which may mimic acute appendicitis. Its diagnosis is often delayed, and its occurrence carries an increased risk of significant complications, such as perforation. Case Presentation. A 23-year-old woman presented with sudden onset, severe, right lower quadrant abdominal pain and nausea. Her WBC was elevated, and abdominal CT showed findings indicative of acute appendicitis with a 13 mm fluid-filled appendix and local strand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…The progression from diverticulosis to diverticulitis might occur as a result of a partial or complete obstruction of the appendix [12]. Histopathologically, AD is classified as congenital (true diverticula), which includes all the layers of the appendiceal wall (mucosa, submucosa, muscularis layer, and serosa), or acquired (false diverticula), which includes all the layers except the muscular layer [2].…”
Section: Discussionmentioning
confidence: 99%
“…The progression from diverticulosis to diverticulitis might occur as a result of a partial or complete obstruction of the appendix [12]. Histopathologically, AD is classified as congenital (true diverticula), which includes all the layers of the appendiceal wall (mucosa, submucosa, muscularis layer, and serosa), or acquired (false diverticula), which includes all the layers except the muscular layer [2].…”
Section: Discussionmentioning
confidence: 99%
“…Identification of AD on CT can be difficult because of the associated inflammatory changes [ 19 ]. Histopathological diagnosis is very important to follow as the clinical and radiological differentiation between AD and acute appendicitis is difficult [ 1 , 4 , 20 ]. Our case was only a histopathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Appendicular mucocele most likely to be in elderly women with variable presentations, which differ from AD that tends to be asymptomatic in male patient unless they present with inflammatory changes [ 9 ]. Images might help in the differentiation between AD and MAN; the classical CT abdomen finding of AD is: appendiceal diverticulum with hyperdense pericaecal fat [ 2 ] compared with a thin capsulated cystic mass in the right lower quadrant with low attenuation and wall calcification for MAN [ 10 ]. Colonoscopy also has some ability in identifying appendicular mucocele if the appendiceal orifice is seen at the center of the mound, which is known as ‘Volcano sign’ [ 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…Appendicular diverticulum (AD) is considered as one of the rare entities, which was firstly reported in 1893 by Kelynack, and its reporting incidence is up to 2% [ 1 ]. Despite that AD is a pathological diagnosis, clinically and radiologically it can mimic acute appendicitis (AA) [ 1 , 2 ]. Toh et al [ 3 ] has reported a remarkable increase of malignancy rate and complications such as perforation in association of the AD.…”
Section: Introductionmentioning
confidence: 99%